TREATMENT APPROACHE FOR ODONTOGENIC CYSTS IN THE MAXILLA - Markovska Arsovska, Mirjana; Terzievski, Goran; Simjanovska, Ljuba; Gerasimova Pisevska, Sofijanka; Stojanova, Irena (Journal of Morphological Sciences, 2022)
A cyst is defined as a pathological cavity lined by epithelium. The epithelium itself is surrounded by fibrocollagenous connective tissue and may be derived from various sources. They are usually associated with carious, nonvital, discolored, or fractured teeth and are found mostly at the apices of the teeth. Radiologically, it arises from the apex of the root of a carious tooth and is bounded by a thin rim of cortical bone. They rarely become problematic and are incidentally found on routine dental radiographs. As they appear to reach a considerable size prior to medical attention due to their insidious and destructive growth characteristics during the intraosseous stage, treatment often requires extensive cystectomy and skeletal reconstruction. This case report shows the treatment of a big radicular cyst in the maxilla . After surgical enucleation and biopsy, histopathological picture revealed fragments of sections of a collagen cyst wall lined with multilayered squamous epithelium which were seen microscopically. Scarce inflammation is present. Immunohistochemically was found focal CD20+ lymphoid accumulations (up to 40%) with CD3+ T lymphocytes up to 60% of which a significant part is CD40+, and 10% CD8+, CD68 mark the reduced presence of resident histiocytes (up to 5%). The finding confirmed the presence of a chronically inflamed radicular cyst. Keywords: radicular cyst, imunohistochemistery, cystectomy, cyst diagnosis, cyst biopsy